2014
DOI: 10.1542/peds.2013-1886
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Early Infant Sleep and Crying Problems and Postnatal Depression: A Randomized Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Infant sleep and crying problems are common and associated with postnatal depression. No programs aiming to prevent all 3 issues have been rigorously evaluated. WHAT THIS STUDY ADDS:A prevention program targeting these issues improves caregiver mental health, behaviors, and cognitions around infant sleep. Implementation at a population level may be best restricted to infants who are frequent feeders because they experience fewer crying and daytime sleep problems. abstract OBJECTIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(186 citation statements)
references
References 33 publications
5
181
0
Order By: Relevance
“…There also is an association between infant sleeping problems and PPD, which may be mediated via disruption in women’s sleep (Armstrong et al 1998; Bayer et al 2007; Dennis and Ross 2005; Hiscock and Wake 2001). To date, including the treatment of infant behaviors in PPD interventions is only beginning (Hiscock and Wake 2002; Hiscock et al 2014). …”
Section: Risks For Ppd Including Infant Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…There also is an association between infant sleeping problems and PPD, which may be mediated via disruption in women’s sleep (Armstrong et al 1998; Bayer et al 2007; Dennis and Ross 2005; Hiscock and Wake 2001). To date, including the treatment of infant behaviors in PPD interventions is only beginning (Hiscock and Wake 2002; Hiscock et al 2014). …”
Section: Risks For Ppd Including Infant Behaviorsmentioning
confidence: 99%
“…In the first of its kind, Hiscock et al (2014) provided 781 mother-infant dyads with written materials and an educational DVD that presented information about infant sleep cycles and crying patterns, strategies to promote independent settling (e.g., swaddling), and information about self–care for parents. Mothers in the intervention group were significantly less likely to meet criteria for possible depression (>9 on the Edinburgh Postnatal Depression Scale) when their infant was 6 months old, though there were no differences between the intervention and control groups at 4 months postpartum.…”
Section: Infant Sleep and Cry Interventionsmentioning
confidence: 99%
“…First, data suggest that disturbed sleep in newborns and infants is associated with a new onset of depressive symptoms in mothers [11,15], and maternal depression scores are not identified as predictors of later child sleep problems in long-term studies [6]. Second, findings indicate that the treatment of the child´s sleep problem can simultaneously improve maternal depression scores [16][17][18][19][20] and maternal stress or marital satisfaction [21]. Research including data on both parents is quite rare.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies demonstrate the efficacy of behavioral interventions in reducing pediatric sleep disturbances [21,35] and in improving parental strain [16][17][18][19][20]. Personal support (face-to-face or telephone support) seems to increase improvements in parental psychosocial health [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Most controlled trials of educational sleep interventions for postnatal dyads have focused on the quality of infants’ sleep, and on balance these trials have not shown major benefits 81. Among the minority of trials that examined maternal depressive symptoms as an outcome, most studies reported positive results 828384. One notable pilot RCT of 30 postpartum women found that women who received a sleep counseling intervention averaged more night-time sleep than controls (57 (95% confidence interval 6 to 106) min; P=0.03) 85.…”
Section: Personalized Treatment For Specific Clinical Characteristicsmentioning
confidence: 99%